(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current research aimed to identify the level of moral identity and social affiliation among students exposed to shock pressures, as well as to reveal the relationship between these variables. To achieve these objectives, the researcher adopted the diagnostic tool for the measure of post-traumatic stress disorder (PDS-5) scale (Foa, 2013) translated to Arabic language by (Imran, 2017). The researcher also adopted the moral identity scale built by (Al-Bayati, 2015) and the measure of social affiliation built by (Al-Jashami, 2013), which were applied to a random sample of (200) male and female students chose from al Anbar University. They were exposed to shock pressures. The results of the research showed that the sample has an average level of moral identity, and the degrees of the sample members have approached the level of the hypothetical medium. Moreover, the sample has an average level of social affiliation, and the average scores of the sample on the social affiliation scale were not statistically significant. Finally, there is a positive correlation between moral identity and social affiliation.